Analisis Faktor Yang Mempengaruhi Keputusan Ekonomi Rumahtangga Dalam Produksi Dan Pendapatan - Sutarni Sutarni1 (Jurnal Ilmiah ESAI, 2007)
This research was conduct to know the factors influencing household economic decision in production for aquaculture and family income.  The economic model was build at simultaneous econometric model through by Statistical Analysis System (SAS).  The farmer household usually got family income from aquaculture and another.  Aquaculture production depended on seed cost, feeding cost, and family labor allocation.  Based on the elasticity value, the aquaculture production was not responsive to independent variable which is influenced it.  Aquaculture income influenced by aquaculture production, aquaculture cost production, and age of respondent. Based on the elasticity value, the aquaculture income was responsive to aquaculture production and aquaculture cost production.  Another family income influenced by age, education, and labor of family allocation.  Based on the elasticity value, another family income was responsive to education and labor of family allocation. Kata kunci: keputusan ekonomi, produksi, pendapatan dalam usaha, Pendapatan luar usaha